Introduction to machine learning and bioinformatics - Mitra, Sushmita 1962- (Series in computer science and data analysis, 2008)
"Shedding light on aspects of both machine learning and bioinformatics, this text shows how the innovative tools and techniques of machine learning help extract knowledge from the deluge of information produced by today's biological experiments."--Jacket.